Cigarette smoke and platelet-activating factor receptor dependent adhesion of Streptococcus pneumoniae to lower airway cells. Issue 10 (1st May 2012) - Grigg, Jonathan; Walters, Haydn; Sohal, Sukhwinder Singh; Wood-Baker, Richard; Reid, David W; Xu, Cang-Bao; Edvinsson, Lars; Morissette, Mathieu C; Stämpfli, Martin R; Kirwan, Michael; Koh, Lee; Suri, Reetika; et al.
Abstract : Background: Exposure to cigarette smoke (CS) is associated with increased risk of pneumococcal infection. The mechanism for this association is unknown. We recently reported that the particulate matter from urban air simulates platelet-activating factor receptor (PAFR)-dependent adhesion of pneumococci to airway cells. We therefore sought to determine whether CS stimulates pneumococcal adhesion to airway cells. Methods: Human alveolar (A549), bronchial (BEAS2-B), and primary bronchial epithelial cells (HBEpC) were exposed to CS extract (CSE), and adhesion of Streptococcus pneumoniae determined. The role of PAFR in mediating adhesion was determined using a blocker (CV-3988). PAFR transcript level was assessed by quantitative real-time PCR, and PAFR expression by flow cytometry. Lung PAFR transcript level was assessed in mice exposed to CS, and bronchial epithelial PAFR expression assessed in active-smokers by immunostaining. Results: In A549 cells, CSE 1% increased pneumococcal adhesion (p<0.05 vs control), PAFR transcript level (p<0.01), and PAFR expression (p<0.01). Pneumococcal adhesion to A549 cells was attenuated by CV-3988 (p<0.001). CSE 1% stimulated pneumococcal adhesion to BEAS2-B cells and HBEpC (p<0.01 vs control). CSE 1% increased PAFR expression in BEAS2-B (p<0.01), and in HBEpC (p<0.05). Lung PAFR transcript level was increased in mice exposed to CS in vivo (p<0.05 vs room air). Active smokers (n=16) had an increased percentage of bronchial epithelium with PAFR-positive cells (p<0.05 vs never smokers, n=11). Conclusion: CSE stimulates PAFR-dependent pneumococcal adhesion to lower airway epithelial cells. We found evidence that CS increases bronchial PAFR in vivo.